(untitled) (JOURNAL OF ADVANCES IN CHEMISTRY, 2015)
Carbon steel as a relatively cheap material having very high mechanical characteristics is widely used in practically all fields. Regrettably, this alloy undergoes corrosion in practice under the action of such aggressive components as hydrochloric and hydrosulphuric acids, carbon dioxide and many others [1]. Hydrochloric acid is very effective for dissolving calcium carbonate scale inside the pipelines and finds a large application with this goal. There are several ways for decreasing the rate of metals corrosion. One of them is an introduction of inhibitors into acidic systems. The most preferable inhibitors for protection of metals against corrosion are of organic nature and contain such heteroatoms as nitrogen, oxygen, phosphorus and sulphur as well as aromatic rings and multiple bonds. Among various groups of inhibitors surface-active inhibitors are characterized by high levels of inhibition efficiency, cheapness, relative harmlessness and easiness of production. Inhibition was reported to be realized as a result of adsorption of the surfactant molecules, with an aid of their functional groups, to the metal surface [2–5].Presence of such heteroatoms as nitrogen, sulfur and oxygen, because of their tendency to be adsorbed at the metal/media interface with formation of protective layer, is very important [6-8]. Inhibition of iron corrosion by surfactants may occur via two phenomena consisting in blocking and hydrophobing effects [9].As is known, inhibitors are considered to be optimal if they are based on relatively cheap and non-toxic initial components and contain the above-shown heteroatoms and fragments. From this standpoint vegetable oils are very convenient raw materials as they are restorable and ecologically clean [10-13]. In the present study weight loss measurements were performed to examine the H2S acid corrosion inhibition process of carbon steel by some surfactants synthesized on the basis of flaxseed oil and such ethanolamines as monoethanolamine (MEA), diethanolamine (DEA) and triethanolamine (TEA) for the range of concentrations below the critical micelle concentration. Similar surfactants were synthesized and studied as chemicals for removing thin petroleum films from water surface [14]. Meanwhile, the values of interfacial tension at the water-kerosene border in the presence of the synthesized surfactants have been determined and respective colloidal-chemical parameters have been computed.